Discordance Between Triglycerides, Remnant Cholesterol and Systemic Inflammation in Patients with Schizophrenia - Jeffrey Wang; Maaike Kockx; Gabrielle J. Pennings; Tim Lambert; Vincent Chow; Leonard Kritharides (Biomedicines)
Background/Objectives: Hypertriglyceridaemia and systemic inflammation are prevalent in patients with schizophrenia and contribute to an increased risk of cardiovascular disease. Although elevated triglycerides (TGs) and remnant cholesterol are linked to inflammation in the general population and individuals with metabolic syndrome, whether they are associated in patients with schizophrenia remains unclear. Methods: Fasting levels of TG, cholesterol (total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and remnant cholesterol)), and markers of systemic inflammation including high-sensitivity C-reactive protein (hsCRP), leukocyte counts and their differentials (neutrophils, monocytes and lymphocytes) were determined in 147 patients diagnosed with schizophrenia on long-term antipsychotic regimens and compared with 56 age- and sex-matched healthy controls. Apolipoprotein B and glycosylation of acute phase reactant (GlycA) signatures were assessed by NMR. Circulating cytokine levels were measured by a cytokine/chemokine multiplex assay. Results: Patients with schizophrenia had markedly elevated TG and remnant cholesterol relative to controls and had evidence of systemic inflammation with increased circulating hsCRP, GlycA, leukocyte, neutrophil counts and neutrophil-to-lymphocyte ratio (NLR). Unexpectedly TG and remnant cholesterol did not correlate with systemic inflammatory markers in patients with schizophrenia, and differences in inflammatory markers between controls and patients persisted after adjusting for the lipid profile. Interleukin (IL)-10 levels were increased in patients with schizophrenia, suggesting an anti-inflammatory signature. Conclusions: The discordance between TG, remnant cholesterol and systemic inflammation in patients with schizophrenia suggests these are likely independent contributors to cardiovascular risk in this population.